2017
DOI: 10.1088/2058-9565/aa7b65
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing a quantum dot with a spontaneous parametric down-conversion source

Abstract: Quantum networks require interfacing stationary and flying qubits. These flying qubits are usually nonclassical states of light. Here we consider two of the leading source technologies for nonclassical light, spontaneous parametric down-conversion and single semiconductor quantum dots. Downconversion delivers high-grade entangled photon pairs, whereas quantum dots excel at producing single photons. We report on an experiment that joins these two technologies and investigates the conditions under which optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This work shows the reliability and versatility of the implemented platform, merging and interfacing technologically different solutions in the same network. The use of separable measurements allows interfacing sources of different natures, avoiding the drawbacks of optical Bell-state measurements requiring also the synchronization of single-photon emission [96]. Furthermore, our experiment has employed both free-space and fiber links in an urban environment, whose combined adoption represents a crucial requirement towards large scale networks.…”
Section: Discussionmentioning
confidence: 99%
“…This work shows the reliability and versatility of the implemented platform, merging and interfacing technologically different solutions in the same network. The use of separable measurements allows interfacing sources of different natures, avoiding the drawbacks of optical Bell-state measurements requiring also the synchronization of single-photon emission [96]. Furthermore, our experiment has employed both free-space and fiber links in an urban environment, whose combined adoption represents a crucial requirement towards large scale networks.…”
Section: Discussionmentioning
confidence: 99%
“…This work shows the reliability and versatility of the implemented platform, merging and interfacing technologically different solutions in the same network. The use of separable measurements allows interfacing sources of different natures, avoiding the drawbacks of optical Bell-state measurements requiring also the synchronization of the single-photon emission [93]. Furthermore, our experiment has employed both free-space and fiber links in an urban environment, whose combined adoption represent a crucial requirement towards large scale networks.…”
mentioning
confidence: 99%
“…Here we explore both theoretically and experimentally HOM interference with imperfect single-photon sources. Previously, the impact of multi-photon contributions on HOM interference has been investigated in the limited case where the additional photons are in the same spectral and temporal mode as the predominant ones [20][21][22]. It has been shown that the visibility of HOM interference in this case is given by V HOM = M tot − g (2) (0) [19,23], where M tot is the mean wavepacket overlap of the total input state, i.e.…”
mentioning
confidence: 99%